Nature of Violence - Chandel, Bhuvan (Ed.) (Chandigarh, 1980)
"Nature of Violence" is an attempt on the part of the Department of Philosophy to assert a fundamental coherence to the deliberations of a seminar "On Violence" which was held under the auspices of the Department a couple of years back, The predominant interest of the Department (as per the reports of the U.G.C. visiting committees) has been in the area of social philosophy ever since its inception in 1959. Therefore it is not surprising that the present volume singles out one of the most important areas of social philosophy for a special consideration. One cannot but agree with Hannah Arendt when she says "No one engaged in thought about history and politics can remain unaware of the enormous role violence has played in human affairs".
Keywords: Violence